2007
DOI: 10.1007/s00216-007-1754-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cocaine and its principal metabolites in waste and surface water using solid-phase extraction and liquid chromatography–ion trap tandem mass spectrometry

Abstract: A validated method based on solid-phase extraction (SPE) and liquid chromatography-ion trap tandem mass spectrometry (LC-MS/MS) is described for the determination of cocaine (COC) and its principal metabolites, benzoylecgonine (BE) and ecgonine methyl ester (EME), in waste and surface water. Several SPE adsorbents were investigated and the highest recoveries (95.7 +/- 5.5, 91.8 +/- 2.2 and 72.5 +/- 5.3% for COC, BE and EME, respectively) were obtained for OASIS HLB(R) cartridges (6 mL/500 mg) using 100 mL of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
130
1
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(142 citation statements)
references
References 31 publications
7
130
1
4
Order By: Relevance
“…The pH adjustment was found to be necessary to prevent degradation of COC, BE and EME during transport and storage (Gheorghe et al, 2008). The sample collection took place from June 2007 until February 2008.…”
Section: Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pH adjustment was found to be necessary to prevent degradation of COC, BE and EME during transport and storage (Gheorghe et al, 2008). The sample collection took place from June 2007 until February 2008.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Recently, a new, direct and objective way of monitoring drug consumption has been proposed, based on the measurement of urinary excreted drugs and their metabolites in waste and surface water (Bones et al, 2007;Castiglioni et al, 2006;Gheorghe et al, 2008;Huerta-Fontela et al, 2007;Hummel et al, 2006;KasprzykHordern et al, 2008a,b;Zuccato et al, 2005Zuccato et al, , 2008. While these studies are particularly based on measurements by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS), they differ on the sample preparation approaches and the groups of investigated drugs of abuse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known however, that the use of psychoactive substances is essentially universal and that they are one of the most recent additions to the list of contaminants of emerging concern in the environment (Boleda et al, 2009;Kasprzyk-Hordern et al, 2010). It is clear from the studies that have identified these compounds in wastewater effluents and surface waters at the nanogram and in some cases, microgram per liter level, that they and many of their main human metabolites, are ubiquitous in the environment (Baker and Kasprzyk-Hordern, 2011;Bartelt-Hunt et al, 2009;Bijlsma et al, 2012Bijlsma et al, , 2013Castiglioni et al, 2006a;Gheorghe et al, 2008;González-Mariño et al, 2011;Hummel et al, 2006;Jones-Lepp et al, 2004;Kasprzyk-Hordern et al, 2009;Metcalfe et al, 2010;Pedrouzo et al, 2011a;Postigo et al, 2011;Zuccato et al, 2005). In fact, these compounds, like many other contaminants of emerging concern have been shown to be resistant to physicochemical and biological treatment at WWTPs and are therefore continuously introduced into the aquatic environment (Boleda et al, 2009;Bolong et al, 2009;Chiaia et al, 2008;Huerta-Fontela et al, 2008;Pal et al, 2013;Postigo et al, 2010;Valcárcel et al, 2012;Yargeau et al, 2013;Zuccato et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1 along with some physicochemical properties of the selected compounds. These DOAs were selected based on their worldwide consumption (UNODC, 2008) and detection in wastewater effluents in a previous Canadian study as well as in studies conducted in other countries (Boleda et al, 2007;Bones et al, 2007;Castiglioni et al, 2006b;Gheorghe et al, 2008;HuertaFontela et al, 2007;Hummel et al, 2006;Irvine et al, 2011;KasprzykHordern et al, 2009;Metcalfe et al, 2010;Pedrouzo et al, 2011a;Postigo et al, 2011;Zuccato and Castiglioni, 2009). In addition, it has been shown that COC has cyto-genotoxic effects on Dreissena polymorpha (zebra mussel) at environmentally relevant concentrations.…”
Section: Introductionmentioning
confidence: 99%